Hydrophilic treatment method of polyethylene porous diaphragm and application of hydrophilic treatment method in organic flow battery
By hydrophilic treatment of the polyethylene porous separator, a hydrophilic polyethylene porous separator with a pore size of 30-50nm is formed, and it is used in organic liquid flow batteries. It solves the problem of short circuit and electrolyte mixing caused by the easy puncture or defects of the anion exchange membrane, extends the service life of the battery and improves the circulation stability.
Patent Information
- Application Number
- CN202510086319.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The anion exchange membrane in organic liquid flow batteries is susceptible to the problem of positive and negative electrode short circuit and electrolyte mixing caused by puncture of carbon felt electrodes or defects, resulting in a decrease in battery capacity and shortening service life.
A hydrophilic treatment method of polyethylene porous separator is adopted. By immersing a polyethylene porous separator in a hydrophilic polymer material solution and treating it in deionized water, a hydrophilic polyethylene porous separator with a pore size of 30-50 nm is obtained, and placed between the anion exchange membrane and the negative electrode carbon felt.
It effectively suppresses local short circuit of positive and negative electrodes and the problem of mixing positive and negative electrodes caused by the anion exchange membrane being pierced by carbon felt electrodes or having defects, extends the service life of organic liquid flow batteries, and significantly improves the cycle stability of the battery.
Smart Images

Figure CN119875196A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic liquid flow batteries, and in particular to a method for hydrophilic treatment of a porous diaphragm for protecting an ion exchange membrane in a liquid flow battery and an application thereof in an organic liquid flow battery. Background Art
[0002] Organic flow battery is a new type of energy storage technology, in which the anion exchange membrane is a key component, which not only separates the positive and negative electrolytes, but also plays the role of conducting anions to form a circuit inside the battery. However, during the operation of the flow battery, the anion exchange membrane is easily pierced by the longitudinal carbon fibers of the carbon felt electrode, or its own defects, causing the positive and negative electrodes of the battery to directly contact, causing the battery to short-circuit, and the electrolytes inside the battery may mix with each other, resulting in a decrease in battery capacity and a shortened service life. Once the flow battery diaphragm is found to be damaged, the battery should be stopped immediately and replaced with a new diaphragm. While replacing the diaphragm, other components of the battery, such as electrodes, electrolytes, etc., should be checked to ensure that they are in normal condition. The cost of replacing the diaphragm has greatly increased the cost of the flow battery. Therefore, protecting the ion exchange membrane and extending its service life has become one of the important research directions.
[0003] The Chinese patent with patent number CN116864724A provides a diaphragm for protecting the ion exchange membrane in the liquid flow battery to protect the perfluorosulfonic acid membrane. However, this double-sided protection method increases the thickness of the diaphragm, increases the ion migration distance, and significantly increases the ion migration resistance, reducing the battery energy efficiency; on the other hand, the pore size of the protective membrane is too large (micrometer level), which cannot solve the problem of cross-contamination of the positive and negative electrolytes of the defective microporous diaphragm, thereby causing battery failure. Summary of the invention
[0004] The purpose of the present invention is to provide a polyethylene porous membrane with a microporous structure and hydrophilicity, which is added between the anion exchange membrane and the negative electrode carbon felt. The hydrophilic porous membrane has a nanometer-level pore size, which can effectively inhibit the ion exchange membrane from being pierced by the carbon felt electrode or the defective anion membrane from causing the local short circuit of the positive and negative electrodes and the mixing of the positive and negative electrolytes, and prevent the membrane from being seriously damaged during the circulation of the flow battery, causing the battery to be seriously short-circuited, and improve the reliability of the flow battery. In addition, the polyethylene porous membrane treatment process proposed in the present invention can reduce the pore size of the porous membrane, greatly inhibit the penetration of the electrolyte, and significantly improve the cycle stability of the battery.
[0005] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for hydrophilic treatment of a polyethylene porous diaphragm, comprising the following steps: The polyethylene porous membrane is immersed in a solution containing a hydrophilic polymer material, and after being completely soaked, the soaked polyethylene porous membrane is immersed in deionized water to obtain a hydrophilic polyethylene porous membrane. After the hydrophilic treatment of the porous membrane, it is washed with deionized water and then can be directly used with or without drying. Furthermore, the drying temperature range after washing with deionized water is 50-90°C.
[0006] Furthermore, the polyethylene porous membrane can be a PE membrane used in lithium batteries or a ceramic membrane based on such PE coating.
[0007] Furthermore, the polyethylene porous membrane has a thickness of 7-20 um and a pore size of 30-50 nm.
[0008] Furthermore, the hydrophilic polymer material is ethylene-vinyl alcohol copolymer, and the solvent of the hydrophilic polymer material solution is one or more of nitrogen-methyl pyrrolidone, dimethyl sulfoxide, and dimethylformamide.
[0009] Furthermore, the concentration of the hydrophilic polymer material in the hydrophilic polymer material-containing solution is 0.5wt.%-1.5wt.%.
[0010] The present invention also provides a hydrophilic polyethylene porous diaphragm prepared by the hydrophilic treatment method as described above.
[0011] The present invention also provides application of the hydrophilic polyethylene porous diaphragm in an aqueous organic liquid flow battery.
[0012] Furthermore, the hydrophilic polyethylene porous diaphragm is placed between the ion exchange membrane and the negative electrode carbon felt in the battery, and its size is consistent with that of the ion exchange membrane. The hydrophilic diaphragm of the present invention is attached between the anion exchange membrane and the negative electrode carbon felt of the aqueous organic liquid flow battery, which solves the problem of battery short circuit and mixing of positive and negative electrolytes caused by the carbon felt electrode piercing the anion exchange membrane and the defects of the anion membrane, thereby extending the service life of the aqueous organic liquid flow battery.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The hydrophilic treatment preparation process of the polyethylene porous diaphragm of the present invention is simple to operate, has low cost, and is suitable for large-scale production.
[0014] The polyethylene porous diaphragm of the present invention has a uniform microporous structure with a pore size of 30-50nm. After a unique hydrophilic treatment, the water-insoluble hydrophilic agent ethylene-vinyl alcohol copolymer can further reduce the pore size of the polyethylene porous diaphragm, thereby enhancing the ability to block electrolyte penetration and significantly improving the battery life.
[0015] The hydrophilic membrane of the present invention has strong hydrophilicity, good wettability in the aqueous organic liquid flow battery electrolyte, good stability, and good conductivity, and will not significantly reduce the battery energy efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Assemble the structural diagram for the existing flow battery anion membrane and carbon felt; Figure 2 The assembly structure diagram of the anion membrane and carbon felt of the flow battery after adding the hydrophilic polyethylene porous diaphragm to the embodiment of the present invention; Figure 3 This is a diagram of the capacity retention rate of the diaphragm battery test in Example 1 of the present invention; Figure 4 This is a diagram of the capacity retention rate of the diaphragm battery test in Example 2 of the present invention; Figure 5 This is a diagram of the capacity retention rate of the diaphragm battery test in Example 3 of the present invention; Figure 6 This is a diagram of the capacity retention rate of the diaphragm battery test in Example 4 of the present invention; Figure 7 This is a comparison chart of pore size distribution of the polyethylene porous diaphragm without hydrophilic treatment, directly dried after hydrophilic treatment, and washed and dried after hydrophilic treatment in Examples 2 to 4 of the present invention; Figure 8 This is a scanning electron microscopy image of the surface morphology of the polyethylene porous diaphragm without hydrophilic treatment; Fig. 9 This is a scanning electron microscope image of the surface morphology of the hydrophilic polyethylene porous diaphragm that was directly dried at 60° C. without washing in Example 2; Fig.10 This is a scanning electron microscopy image of the surface morphology of a hydrophilic polyethylene porous diaphragm that was dried at 60°C without washing; Fig.11 This is a scanning electron microscope image of the surface morphology of the hydrophilic polyethylene porous diaphragm after washing and not drying in Example 3; Fig.12 This is a scanning electron microscope image of the surface morphology of the hydrophilic polyethylene porous diaphragm in Example 4 after washing with water and drying at 60°C. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The embodiments of the present invention are applied to liquid flow batteries, and the organic liquid flow energy storage battery of the TEMPO-MV system with the greatest commercial potential is selected as an example for explanation, but the application of the scheme described in the present invention in other liquid flow batteries is not limited.
[0019] Single cell performance test conditions: (1) Current density: 80mA / cm 2 ; (2) Charge and discharge experiment: charge to 1.5V, discharge to 0.9V; (3) Electrode parameters: thickness 4 mm, assembly compression rate 20%, effective working area 49 cm 2 ; (4) Anion exchange membrane: Suqian Times Energy Storage Technology Co., Ltd., QPAT membrane, thickness 50 μm; (5) Electrolyte: 50 ml of 1.5 M TEMPO aqueous solution for the positive electrode and 50 ml of 1.5 M MV aqueous solution for the negative electrode; (6) Other conditions: Laboratory temperature 25±2℃, positive and negative electrode pump speeds both 35r / min. Example 1
[0020] The separator of the single cell is a 50μm QPAT ion membrane, and the assembly structure of the ion membrane and carbon felt is the same. Figure 1 The test results are as follows: Figure 3 As shown, it can be seen that the capacity of the battery cell decays by 4% in the first 300 weeks; the capacity decay is relatively fast. The presumed reason is that the QPAT ion membrane is easily pierced by the longitudinal carbon fibers of the carbon felt electrode or has defects itself, and the electrolyte penetrates quickly. The permeability coefficient is detailed in Table 1. Example 2
[0021] The diaphragm of the single cell is a 50μm QPAT ion membrane and a 7μm thick hydrophilic polyethylene porous diaphragm with a pore size range of 30~50nm. The hydrophilic treatment method of the polyethylene porous diaphragm is as follows: the polyethylene porous diaphragm is immersed in a solvent of dimethyl sulfoxide and 1% mass concentration of ethylene-vinyl alcohol copolymer. After complete infiltration, the hydrophilic agent on the surface of the porous diaphragm is wiped off with dust-free paper and dried at 60°C. The QPAT ion membrane, hydrophilic polyethylene porous diaphragm and carbon felt assembly structure are the same. Figure 2 The test results are as follows: Figure 4 As shown, it can be seen that the capacity of the battery cell decays by 4% in the first 300 weeks; the capacity decay is fast, which is caused by the presence of micro defects in the anion membrane and the surface morphology of the hydrophilic polyethylene porous membrane treated by direct drying ( Fig. 9 ) and the surface morphology of the polyethylene porous membrane without hydrophilic treatment ( Figure 8 ) are relatively close, indicating that the hydrophilic agent failed to effectively reduce the pore size of the polyethylene porous membrane ( Figure 7), the penetration of electrolyte is still fast, and the permeability coefficient is shown in Table 1. Example 3
[0022] The diaphragm of the single cell is a 50μm QPAT ion membrane and a 7μm thick hydrophilic polyethylene porous diaphragm with a pore size range of 30~50nm. The hydrophilic treatment method of the polyethylene porous diaphragm is: immerse the polyethylene porous diaphragm in a solvent of dimethyl sulfoxide with a mass concentration of 1% ethylene-vinyl alcohol copolymer. After it is completely soaked, immerse the porous diaphragm in deionized water and use it directly after taking it out. The QPAT ion membrane, hydrophilic polyethylene porous diaphragm and carbon felt assembly structure are the same. Figure 2 The test results are as follows: Figure 5 As shown, it can be seen that the capacity of the battery cell decays by 1% in the first 600 cycles, which significantly inhibits the capacity decay. The reason is that although there are micro defects in the anion membrane, the surface morphology of the polyethylene porous membrane treated by this method ( Fig.11 ) and the surface morphology of the polyethylene porous membrane without hydrophilic treatment ( Figure 8 ), indicating that the water-insoluble hydrophilic agent (ethylene-vinyl alcohol copolymer) is more evenly adsorbed on the pore surface of the polyethylene porous membrane, effectively reducing the pore size of the polyethylene porous membrane and significantly inhibiting the penetration of the electrolyte. The permeability coefficient is shown in Table 1. Example 4
[0023] The diaphragm of the single cell is a 50μm QPAT ion membrane and a 7μm thick hydrophilic polyethylene porous diaphragm with a pore size range of 30~50nm. The hydrophilic treatment method of the polyethylene porous diaphragm is: immerse the polyethylene porous diaphragm in a solvent of dimethyl sulfoxide with a mass concentration of 1% ethylene-vinyl alcohol copolymer. After complete infiltration, immerse the porous diaphragm in deionized water, take it out and dry it at 60°C. The QPAT ion membrane, hydrophilic polyethylene porous diaphragm and carbon felt assembly structure are the same. Figure 2 The test results are as follows: Figure 6 As shown, it can be seen that the capacity of the battery cell decays by 2% in the first 600 weeks, which significantly inhibits the capacity decay. The reason is that there are micro defects in the anion membrane. The surface morphology of the polyethylene porous membrane treated by this method ( Fig.12 ) and the surface morphology of the hydrophilic polyethylene porous membrane treated by direct heating and drying ( Fig.10 ) have significant differences. For the hydrophilic polyethylene porous membrane directly dried, the non-water-soluble hydrophilic agent (ethylene-vinyl alcohol copolymer) is severely agglomerated and cannot be uniformly adsorbed on the pore surface of the polyethylene porous membrane. This once again proves that the hydrophilic treatment method proposed in the present invention can make the non-water-soluble hydrophilic agent (ethylene-vinyl alcohol copolymer) more uniformly adsorbed on the pore surface of the polyethylene porous membrane, effectively reducing the pore size of the polyethylene porous membrane ( Figure 7 ), which significantly inhibited the permeation of the electrolyte. The permeability coefficient is shown in Table 1. Example 5
[0024] This example provides the test data of a single cell in which a hydrophilic polyethylene porous diaphragm treated with ethylene-vinyl alcohol copolymer dimethyl sulfoxide solution (hydrophilic agent) of different concentrations is bonded to a QPAT ion membrane and assembled with a QPAT ion membrane; the diaphragm of the single cell is a 50μm QPAT ion membrane and a 7μm hydrophilic polyethylene porous diaphragm. The hydrophilic treatment method of the polyethylene porous diaphragm is: the polyethylene porous diaphragm is immersed in a solvent of dimethyl sulfoxide, 0.5%, 1% and 1.5% mass concentration of ethylene-vinyl alcohol copolymer, respectively, and after complete infiltration, the porous diaphragm is immersed in deionized water, and taken out and used directly. The energy efficiency of a single cell is shown in Table 2. The energy efficiencies of the single cells treated with 0.5%, 1% and 1.5% mass concentrations of ethylene-vinyl alcohol copolymer hydrophilic agent bonded to the QPAT ion membrane and assembled with the QPAT ion membrane are 80.5%, 81%, 80.6% and 81.5%, respectively, indicating that 0.5%-1.5% mass concentrations of ethylene-vinyl alcohol copolymer hydrophilic agent have little effect on the resistance of the polyethylene porous membrane. Example 6
[0025] This embodiment provides the test data of single cells assembled with QPAT ion membrane and QPAT ion membrane of different thicknesses of polyethylene porous diaphragm; the diaphragm of the single cell is 50μm QPAT ion membrane and hydrophilic polyethylene porous diaphragm. The hydrophilic treatment method of the polyethylene porous diaphragm is: the polyethylene porous diaphragms with thicknesses of 7μm, 12μm, 17μm and 20μm are respectively immersed in ethylene-vinyl alcohol copolymer with a mass concentration of 1% as solvent of dimethyl sulfoxide, and after complete infiltration, the porous diaphragm is immersed in deionized water and taken out for direct use. The energy efficiency of the single cell is shown in Table 3. The energy efficiency of the single cell assembled with 7μm, 12μm, 17μm and 20μm polyethylene porous diaphragms treated with hydrophilic agents and QPAT ion membranes is 80.3%, 81%, 81%, 80.5 and 81.5%, respectively, indicating that the resistance difference of 7μm-20μm polyethylene porous diaphragms after hydrophilic treatment is small and can be used. Example 7
[0026] This embodiment provides single-cell test data of polyethylene porous membranes dried at different temperatures and bonded to QPAT ion membranes and QPAT ion membranes; the membranes of the single cell are 50μm QPAT ion membranes and hydrophilic polyethylene porous membranes. The hydrophilic treatment method of the polyethylene porous membranes is: immerse the polyethylene porous membranes with a thickness of 12μm in a solvent of dimethyl sulfoxide and 1% mass concentration of ethylene-vinyl alcohol copolymer, and after complete infiltration, immerse the porous membranes in deionized water, take them out and dry them at 50℃, 60℃, 70℃, 80℃ and 90℃ for use (drying time is 10min). The energy efficiency of a single cell is shown in Table 4. The energy efficiencies of the single cells assembled with the hydrophilic polyethylene porous membrane bonded to the QPAT ion membrane and the QPAT ion membrane dried at 50°C, 60°C, 70°C, 80°C and 90°C are 81.2%, 81.2%, 81.2%, 81.1%, 81.0% and 81.5%, respectively, indicating that the resistance difference of the polyethylene porous membranes dried at 50°C-90°C is small and they can all be used.
[0027] Table 1 Permeability coefficient of the membrane in Examples 1 to 4
[0028] Table 2 Comparison of energy efficiency of polyethylene porous diaphragms treated with hydrophilic agents of different concentrations in single cells in Example 5
[0029] Table 3 Comparison of energy efficiency of polyethylene porous membranes of different thicknesses in single cells in Example 6
[0030] Table 4 Comparison of energy efficiency of hydrophilic polyethylene porous membranes dried at different temperatures in single cells in Example 7
[0031] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0032] It should be noted that the above content only illustrates the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.
Claims
1. A method for hydrophilic treatment of a polyethylene porous diaphragm, characterized in that: The following steps are involved: ; The polyethylene porous diaphragm is immersed in a solution containing a hydrophilic polymer material. After the polyethylene porous diaphragm is completely immersed, the immersed polyethylene porous diaphragm is immersed in deionized water to obtain a hydrophilic polyethylene porous diaphragm.
2. The hydrophilic treatment method for a polyethylene porous diaphragm according to claim 1, characterized in that: The polyethylene porous diaphragm may be a PE membrane used in lithium batteries or a ceramic membrane coated with such PE.
3. The hydrophilic treatment method for a polyethylene porous diaphragm according to claim 1, characterized in that: The thickness of the polyethylene porous membrane is 7-20 um, and the pore size is 30-50 nm.
4. The hydrophilic treatment method for a polyethylene porous diaphragm according to claim 1, characterized in that: The hydrophilic polymer material is ethylene-vinyl alcohol copolymer, and the solvent of the hydrophilic polymer material solution is one or more of nitrogen methyl pyrrolidone, dimethyl sulfoxide, and dimethylformamide.
5. The hydrophilic treatment method for a polyethylene porous diaphragm according to claim 1, characterized in that: The concentration of the hydrophilic polymer material in the hydrophilic polymer material solution is 0.5wt.%-1.5wt.%.
6. A hydrophilic polyethylene porous diaphragm prepared by the hydrophilic treatment method according to any one of claims 1 to 5.
7. Use of the hydrophilic polyethylene porous membrane according to claim 6 in an aqueous organic liquid flow battery.
8. The use according to claim 7, characterized in that: The hydrophilic polyethylene porous separator is placed between the ion exchange membrane and the negative electrode carbon felt in the battery.
Citation Information
Patent Citations
Diaphragm for protecting ion exchange membrane in flow battery and application of diaphragm
CN116864724A